Rapid Quantification of Drug Resistance Gene Expression in Candida albicans by Reverse Transcriptase LightCycler PCR and Fluorescent Probe Hybridization - Frade, Joao P. (American Society for Microbiology, 2004)
We developed a rapid, sensitive, and reproducible assay to quantify Candida albicans ACT1, CDR1, CDR2, ERG11, and MDR1 mRNA using a two-step reverse transcription and LightCycler real-time PCR (RT-LightCycler PCR) method with sequence-specific hybridization probes. We compared RT-LightCycler PCR with Northern hybridization for quantitative analysis of gene expression in isolates with various fluconazole susceptibilities. Specificity of each LightCycler PCR was verified by LightCycler melting curve analysis and agarose gel electrophoresis of amplified products. Correlation of quantification results between RT-LightCycler PCR and Northern hybridization yielded correlation coefficients of ≥0.91 for all genes except MDR1 (0.74). In this case, reduced correlation was due to the inability of Northern hybridization to accurately quantify the high MDR1 expression in a susceptible dose-dependent isolate which was shown by RT-LightCycler PCR to overexpress MDR1 >200-fold relative to the other isolates tested. In four isolates, low levels of CDR2 mRNA were detected by RT-LightCycler PCR but were undetectable by Northern hybridization. mRNA quantification by RT-LightCycler PCR correlates with Northern hybridization and offers additional advantages, including increased sensitivity and speed of analysis, along with lower RNA concentration requirements and an increased dynamic range of signal detection.